Sperm DNA and RNA abnormalities in fertile and oligoasthenoteratozoospermic smokers. (8th May 2012) - Selit, I.; Basha, M.; Maraee, A.; El‐Naby, S. H.; Nazeef, N.; El‐Mehrath, R.; Mostafa, T.
Summary: This study aimed to assess sperm DNA and RNA abnormalities in fertile and oligoasthenoteratozoospermic (OAT) smokers. In all, 140 subjects were included and classified into fertile nonsmokers, fertile smokers, OAT nonsmokers and OAT smokers. They were subjected to history taking, clinical examination, semen analysis, assessment of sperm DNA and RNA abnormalities. The results showed that an increased percentage of abnormal sperm DNA and RNA was demonstrated in fertile smokers compared with fertile nonsmokers and in OAT smokers compared with OAT nonsmokers. Increased percentage of severe, moderate sperm DNA and RNA damage was demonstrated in fertile heavy smokers compared with fertile light smokers and in OAT heavy smokers compared with OAT light smokers. It is concluded that smoking has a negative impact on sperm DNA and RNA abnormalities that is accentuated in heavy smokers compared with light smokers.